Las plataformas digitales y la particularidad de su papel en el Mercado: su actividad económica y las implicancias laborales que se generan como consecuencia de su incorrecta implementación - Calderón Paredes, Cecilia (2021)
In the context of Bill 4243/2018-CR, the Law of Decent Employment that regulates workers on Digital Platforms, the existence of a new business reality dominated by the phenomenon of digital platforms is undeniable. This new dynamic challenges the classic parameters of labor law and puts into debate the existence or not of an employment relationship between the agents participating in it.In this article, and from a commercial-labor perspective, the author outlines the existence of a new ‘platform economy’, identifies the actors involved in it and the dynamics that it incorporates in the market. In the same way, she examines the new signs of employment that could arise in this scenario, as they have been recognized by the Spanish Supreme Court in one of its last decisions regarding the matter: the Glovo case.